Evaluation of Teacher Learning Programs in Education Quality Madrasah Tsanawiyah Negeri 2 Bengkulu City - Fambudi, Dadun Setiawan; Saputra, Govi; Akbarjono, Ali (UIN Fatmawati Sukarno Bengkulu, 2025)
Abstract: The quality of education in Indonesia is still quite concerning. One of the things that is shown by the evaluation of learning that looks perfect on paper, but still fails to provide real insight into what really needs to be improved in the learning program. This study aims to comprehensively evaluate the effectiveness of the teacher learning program implemented at Madrasah Tsanawiyah Negeri 2 Bengkulu City in an effort to improve the overall quality of education. This study uses a descriptive qualitative method, data analysis using the CIPP evaluation model approach (Context, Input, Process, Product). The results of the evaluation of the teacher learning program at MTsN 2 Bengkulu City have shown an increase in the quality of education, this is seen from the learning tools created by teachers that are in accordance with the guidelines, in the learning process teachers are skilled in opening and closing learning in class using various methods so as to improve student achievement in the academic field both at the regional and national levels. Thus, it can be concluded that the teacher learning program at MTsN 2 Bengkulu City has been able to improve the quality of education. Therefore, it can be suggested that to improve the quality of education, evaluation of the teacher learning program must be carried out continuously.Keywords: Evaluation of Teacher Learning Program, Quality of Education, State Islamic Junior High School 2 Bengkulu City. Abstrak: Mutu pendidikan di Indonesia masih cukup memprihatinkan. Salah satunya ditunjukkan dengan evaluasi pembelajaran nampak sempurna diatas kertas, tetapi masih gagal memberikan insight nyata tentang hal-hal yang perlu diperbaiki dalam program pembelajaran. Penelitian ini bertujuan untuk mengevaluasi secara komprehensif efektivitas program pembelajaran guru yang diterapkan di Madrasah Tsanawiyah Negeri 2 Kota Bengkulu dalam upaya meningkatkan mutu pendidikan secara keseluruhan. Penelitian ini menggunakan metode kualitatif deskriptif, analisis data menggunakan pendekatan model evaluasi CIPP (Context, Input, Process, Product). Hasil evaluasi program pembelajaran guru di MTsN 2 Kota Bengkulu telah menunjukkan peningkatan mutu pendidikan, hal ini terlihat dari perangkat pembelajaran yang dibuat oleh guru sudah sesuai dengan pedoman, dalam proses pembelajaran guru sudah terampil dalam membuka dan menutup pembelajaran di kelas dengan menggunakan metode yang beragam sehingga meningkatan prestasi siswa dalam bidang akademik baik tingkat daerah maupun nasional. Dengan demikian, dapat disimpulkan program pembelajaran guru di MTsN 2 Kota Bengkulu sudah mampu meningkatan mutu pendidikan. Disarankan untuk meningkatkan mutu pendidikan, maka evaluasi terdahap program pembelajaran guru harus dilakukan secara terstruktur dan berkelanjutan.Kata kunci: Evaluasi Program Pembelajaran Guru, Mutu Pendidikan, Madrasah Tsanawiyah Negeri 2 Kota Bengkulu.